IDENTIFYING THE MAIN FACTOR OF STUDENTS’ ANXIETY IN LIMITED FACE-TO-FACE LEARNING ENGLISH SPEAKING DURING COVID-19 - Anisa Riska Noerilah; Nina Puspitaloka (Universitas Wiralodra, 2022)
One of the obstacles, particularly speaking anxiety, has a significant impact on someone's ability to speak a foreign language. In fact, because to the Covid-19 pandemic, researchers discovered that students were anxious of speaking English in class in limited face-to-face learning. In light of this context, the purpose of this study was to look at the primary causes and sources of students' anxiety when learning to speak English in limited face-to-face learning due to pandemic Covid-19. A qualitative methodology and descriptive method were used to conduct the research. Six eighth-grade students from a public junior high school in Karawang took part in the study. Two low-level students, two middle-level students, and two high-level students were separated into three groups. Researchers used observation, interview, and documentation to gather data. The result showed that the primary causes of students' concern in learning English speaking, according to this research, were poor pronunciation and a lack of vocabulary. Meanwhile, students' anxiety in learning English speaking came from lack of confidence and nervousness. It implies that it is essential for teachers to be able to fulfill their roles as facilitators in order to minimize students' speaking anxiety in a foreign language classroom.